Effectiveness of Strategic Planning on Developing Performance in Sudanese Higher Education Institutions from Total Quality Perspective: (Case Study Sudan University of Science and Technology) - Elderderi, Siham Haider; Albadawi, Mohamed Ahmed; Abdelhay, Sameh Mohamed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aims to determine the effect of strategic planning on developing performance at the Sudan University of Science and Technology from a comprehensive quality perspective. The researcher used both the descriptive and analytical approaches in this study. The most important assumption is that there is a statistically significant relationship between the strategic vision and the performance of Sudanese higher education institutions from the perspective of total quality. There is a statistically significant relationship between mission and performance in Sudanese higher education institutions from a comprehensive quality perspective. From a comprehensive quality perspective, there is a statistically significant relationship between the goals and the performance of Sudanese higher education institutions. There is a statistically significant relationship between the level of strategic planning and the quality of institutional performance at the University of Sudan for Science and Technology. The study reached many results, including that the mission of the university is flexible and the university has a narrative announced to all employees. The study also concluded with recommendations, including adopting the quality strategy and its principles when preparing the university's strategic plan and seeking to build a vision among workers about the concept and importance of strategic planning. The necessity of optimal utilization of the university’s financial resources The necessity of involving workers in setting the university’s strategic goals.
Keywords: Strategic Planning; Quality; Performance; Mission; Vision